Saptanga theory of the state in Kautilya’s Arthasastra - Prasain, Indira Devi (TUTA Journal, 2024)
This study analyzes Kautilya’s Saptanga theory of the state as delineated in the Arthasastra, a seminal work in Eastern political philosophy by applying secondary data. Kautilya's Arthasastra is widely regarded as a cornerstone of Eastern political science due to its comprehensive examination of various aspects of governance, ranging from statecraft and warfare to diplomacy, ethics, and geopolitics. The text portrays a realistic governance portrayal, depicting a complex administrative structure, taxation systems, and an advanced intelligence apparatus. Kautilya advocated a strong state with a combination of seven limbs; every element is equally important for successive states. Kautilya posits that the state's primary objective is to elevate humanity from its natural state, allowing individuals to practice their religion and maintain private property rights. In Kautilya's conception, the king assumes the role of a moral guardian, ensuring his subjects' justice and welfare. Moreover, Arthasastra advocates for a decentralized governance model, wherein the state exercises control over autonomous organizations, and prevents absolute authority.